Developmental Differences in Probabilistic Reversal Learning: A Computational Modeling Approach - Weiss, Eileen Oberwelland; Kruppa, Jana A.; Fink, Gereon R.; Herpertz-Dahlmann, Beate; Konrad, Kerstin; Schulte-Rüther, Martin (Frontiers in Neuroscience, 2021)
Cognitive flexibility helps us to navigate through our ever-changing environment and has often been examined by reversal learning. Performance in reversal learning can be modeled using computational modeling allowing the investigation of biologically plausible models to infer psychological mechanisms. Although such models are increasingly used in cognitive neuroscience, developmental approaches are still scarce. Additionally, though most reversal learning paradigms have a comparable design regarding timing and feedback contingencies, the type of feedback differs substantially between studies. The present study used hierarchical Gaussian filter modeling to investigate cognitive flexibility in reversal learning in children and adolescents and the effect of various feedback types. The results demonstrate that children make more overall and regressive errors, while less perseverative errors than adolescents. Analyses of the extracted model parameters of the winning model revealed that children seem to use new and conflicting information less readily than adolescents to update their stimulus-reward associations. Furthermore, more subclinical rigidity in everyday life (parent-ratings) is related to less explorative choice behavior during the probabilistic reversal learning task. Taken together, this study provides first-time data on the development of the underlying processes of cognitive flexibility using computational modeling.